Comparison of global-warming potential impact of food waste fermentation to landfill disposal - Noor Intan Shafinas, Muhammad; Rosentrater, Kurt A. (Springer Nature Switzerland, 2020)
Food waste (FW) has been identifed as a critical global issue. The generation of FW is challenging to control because it is driven by various factors. Landflls, the most common fnal destinations for FW, are often associated with negative economic and environmental impact. Most previous studies have found that FW could also contribute to global warming due to GHG emission from decomposition of organic waste, so it is important to divert FW from landflls and fnd a better option such as using it to produce other value-added products. Depending on the particular FW composition, such waste has potential to be used in fermentation technology, so the primary objective of this study is to compare the global-warming potential (GWP) impact of FW fermentation and landfll disposal methods. Life-cycle assessment (LCA) was conducted to determine the efect on environmental of four scenarios: (i) FW fermentation without enzymes and a 2-step distillation system, (ii) FW fermentation without enzymes and a membrane distillation separation process, (iii) FW fermentation integrated with combined heat power (CHP), and (iv) FW in landflls. As expected, all FW fermentation options produced lower GWP impact values than a landflling method. From the overall fermentation process, the lowest total GWP value was 164.1 kg CO2-eq/1 Mg of FW for the second scenario. Membrane distillation is an environmentally sound process, and suggesting that FW can be utilized to produce value-added products in fermentation while minimizing the environmental burden.